Managing Destination Marketing: Effective Strategies for Boosting Visits to Taman Mumbul Tourist Attraction, Sangeh, Bali - Dewi, Putu Rika Arista; Subadra, I Nengah; Mekarini, Ni Wayan; Yuda, Ida Bagus Nyoman Krisna Prawira; Sudarsana, Komang (Language Assistance, 2024)
This study aims to analyse marketing strategies using the STP (segmentation, targeting, and positioning) approach and the marketing mix strategy analysed through the 7Ps, namely product, price, place, promotion, people, physical evidence, and process at Taman Mumbul Sangeh tourist attraction. This research is descriptive in nature, employing data collection techniques such as observation, interviews, and documentation studies. Based on the analysis, two main conclusions can be drawn: (1) the marketing strategy based on STP focuses more on domestic tourists, who are predominantly aged between 12 and 70 years, with marketing promotions conducted through social media platforms like Instagram and word-of-mouth; and (2) Taman Mumbul Sangeh offers unique tourist products such as pancoran solas (purification), Taman Mumbul temple, and a large pond, which are distinctive features of Taman Mumbul Sangeh that should be preserved and maintained. The pricing strategy should be competitive in the market. Marketing efforts utilise social media platforms and word-of-mouth, while also raising community awareness to participate in promoting Taman Mumbul Sangeh tourist attraction.